IMPLEMENTATION OF A PROBLEM-BASED LEARNING MODEL VIEWED FROM STUDENTS LEARNING STYLES ON STUDENTS MATHEMATICAL PROBLEM SOLVING - Mapeni Mapeni; Rahmad Bustanul Anwar; Dwi Rahmawati; Cornelia Victoria Anghel (Universitas Muhammadiyah Lampung, 2026)
Students mathematical problem-solving ability remains a challenge in secondary education, particularly due to the dominance of teacher-centered conventional methods. This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model in relation to students learning styles (visual, auditory, and kinesthetic) on mathematical problem-solving skills. A quantitative approach with a quasi-experimental design was employed, involving 60 eleventh-grade students divided into experimental (PBL) and control (conventional) groups. Research instruments included a problem-solving test and a learning style questionnaire, with data analyzed using Two-Way ANOVA. The results revealed that: (1) there were significant differences in problem-solving abilities based on students learning styles; (2) the PBL model was more effective than the conventional model; and (3) a significant interaction existed between learning models and learning styles in influencing students problem-solving performance. Therefore, implementing PBL in alignment with students learning styles is proven to enhance the effectiveness of mathematics instruction in secondary schools.